Ethnobotany of Javanese Ethnic Garden Plants in Medan City - Jamilah Nasution; Radiansyah Hadi Chandra; Agung Suharyanto (Lakhomi Journal Scientific Journal of Culture, 2021)
The yard of the house is an open environment around the house and is provided to support various social and economic activities related to the owner of the house. The purpose of this study was to determine the types of horticultural crops based on the Javanese in Medan. The survey method used is the survey and interview methods. The result, obtained 12 types of plants that have the potential as medicinal plants and 2 types of plants that have the potential as ornamental plants. All types of plants have medicinal properties, this shows that the home garden has many benefits in providing potential types of plants, especially the daily needs of the family.